2021
DOI: 10.1097/bpb.0000000000000867
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D level, body mass index and fracture risk in children: vitamin D deficiency and fracture risk

Abstract: The objective of this study was to determine the impacts of preventable causes of fracture, such as vitamin D deficiency, disturbed calcium homeostasis and obesity on fracture occurrence in minor traumas. In this way, the effects of relevant parameters on fracture may be further elucidated. A prospective case-control study in children aged 2-18 years children with and without fractures was performed. Participants with a pediatric trauma score higher than 10 presenting to minor trauma were included to exclude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…20 In spite of its role in calcium homeostasis and the known link between 25(OH)D deficiency and rickets, the association between 25(OH)D deficiency and fracture risk has not been fully established. 4,[21][22][23][24][25][26][27][28][29][30] Some studies have examined the high prevalence of 25(OH)D deficiency among children with fractures, and a few of them compared children with fractures to "non-fractured" control subjects. 20,31 A recent meta-analysis by Yang et al 24 found an association between 25(OH)D insufficiency and a higher risk for fractures in children while other studies reported no association between vitamin D deficiency and fractures in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…20 In spite of its role in calcium homeostasis and the known link between 25(OH)D deficiency and rickets, the association between 25(OH)D deficiency and fracture risk has not been fully established. 4,[21][22][23][24][25][26][27][28][29][30] Some studies have examined the high prevalence of 25(OH)D deficiency among children with fractures, and a few of them compared children with fractures to "non-fractured" control subjects. 20,31 A recent meta-analysis by Yang et al 24 found an association between 25(OH)D insufficiency and a higher risk for fractures in children while other studies reported no association between vitamin D deficiency and fractures in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic glucocorticoid use in children with SLE could lead to abnormal bone metabolism and growth [ 6 , 9 , 30 ]. Studies have shown that serum 25(OH)D levels of 15 ng/mL or less are independently associated with a lower bone formation rate and an increased fracture risk [ 31 ] in adults as well as in children [ 32 ]. In our study, higher 25(OH)D levels were found to be positively associated with higher levels of serum calcium and lower levels of phosphorus, which is related to the role of parathyroid hormone in regulating the levels of calcium under the circumstances of vitamin D deficiency and hypocalcemia [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Varkal et al [1] quoted Kelley et al [4] as a reference for their statement that obesity is associated with increased fracture risk in childhood. However, Kelley et al [4] claimed that obese adolescents ≥10 to <15 years of age (childhood is defined as 3-11 years of age) have an increased fracture risk without investigating fractures in their study.…”
mentioning
confidence: 99%
“…Varkal et al [1] referenced Goulding et al [6] as evidence for children with obesity and high BMI having a higher fracture frequency but the latter authors [6] identified that there was no significant difference in BMI, weight or fat and lean mass between the fracture and nonfracture group. Goulding et al [7] listed four risk factors for forearm fractures which were over-represented in observed versus expected percentages of which obesity was the weakest variable (33.3 versus 15.5%) compared to low dietary calcium intake (20 versus 4.5%), adverse symptoms to cow milk (22.2 versus 6.7%) and early age of first fracture (27.7 versus 11.3%).…”
mentioning
confidence: 99%
See 1 more Smart Citation